2018
DOI: 10.1002/anie.201712141
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid‐Catalyzed Carbonyl‐Olefin Metathesis inside a Self‐Assembled Supramolecular Host

Abstract: Carbonyl-olefin metathesis represents a powerful yet underdeveloped method for the formation of carbon-carbon bonds. So far, no Brønsted acid based method for the catalytic carbonyl-olefin metathesis has been described. Herein, a cocatalytic system based on a simple Brønsted acid (HCl) and a self-assembled supramolecular host is presented. The developed system compares well with the current benchmark catalyst for carbonyl-olefin metathesis in terms of substrate scope and yield of isolated product. Control expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 39 publications
3
88
1
Order By: Relevance
“…In as imilarw ay,T iefenbacher and Catti showed that hexameric CR 6 and cocatalyst HCl worked in as ynergistic wayt o catalyzec arbonyl-olefin metathesis reactions. [18] An example of the capsulee ffect on the chemo-andr egioselectivity of an organic reaction has been reported by Reek et al (Scheme 3). [19] The authors studied the hydration of 11 (66 mm)i nt he presence of CR 6 as an anoreactor (33 mm with respectt o1)a nd 10 (3.3 mm)a sacatalyst (Scheme 3) in water-saturated C 6 D 6 at 70 8C.…”
Section: Hexameric Resorcinarene Capsules As Nanoreactorsmentioning
confidence: 92%
“…In as imilarw ay,T iefenbacher and Catti showed that hexameric CR 6 and cocatalyst HCl worked in as ynergistic wayt o catalyzec arbonyl-olefin metathesis reactions. [18] An example of the capsulee ffect on the chemo-andr egioselectivity of an organic reaction has been reported by Reek et al (Scheme 3). [19] The authors studied the hydration of 11 (66 mm)i nt he presence of CR 6 as an anoreactor (33 mm with respectt o1)a nd 10 (3.3 mm)a sacatalyst (Scheme 3) in water-saturated C 6 D 6 at 70 8C.…”
Section: Hexameric Resorcinarene Capsules As Nanoreactorsmentioning
confidence: 92%
“…Fujita and co‐workers reported an early example of a Pd‐based octahedral cage catalyzing the Diels–Alder reaction . Recently Tiefenbacher and Catti published a study of catalytic carbonyl–olefin metathesis through the combined action of HCl and a self‐assembled supramolecular host . Organometallic catalysts can also be introduced into assemblies to facilitate catalytic reactions by bringing together the catalyst and the substrate .…”
Section: Methodsmentioning
confidence: 99%
“…Artificial supramolecular catalysts are particularly well adapted to regulation, and have proven useful in a wide variety of synthetic contexts . Many metal–organic cages have been developed as supramolecular catalysts, where a substrate enters, is transformed, and exits again. Fujita and co‐workers reported an early example of a Pd‐based octahedral cage catalyzing the Diels–Alder reaction .…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Upon binding to a Lewis acid catalyst, such as FeCl3, the carbonyl functionality is activated to perform a [2+2]-cycloaddition forming an intermediate oxetane, which subsequently undergoes a retro-[2+2]-cycloaddition resulting in the desired metathesis product. While successful protocols for intramolecular and intermolecular Lewis acid-catalyzed carbonyl-olefin metathesis have been reported following this reaction design principle, 7,8 all current procedures rely exclusively on aryl carbonyls as substrates while the reaction of aliphatic ketones remain elusive. [4][5][6][7][8] We report herein the development of a catalytic carbonyl-olefin ring-closing metathesis of aliphatic ketones that proceeds in yields up to 94% and tolerates a variety of functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…While successful protocols for intramolecular and intermolecular Lewis acid-catalyzed carbonyl-olefin metathesis have been reported following this reaction design principle, 7,8 all current procedures rely exclusively on aryl carbonyls as substrates while the reaction of aliphatic ketones remain elusive. [4][5][6][7][8] We report herein the development of a catalytic carbonyl-olefin ring-closing metathesis of aliphatic ketones that proceeds in yields up to 94% and tolerates a variety of functional groups. Mechanistic investigations reveal a distinct mode of activation for aliphatic ketones relative to their aromatic analogs in which the formation of a homobimetallic singly-bridged iron(III)-dimer as the active catalytic species enables the formation of a significantly enhanced electrophilic moiety.…”
Section: Introductionmentioning
confidence: 99%